2019
DOI: 10.1002/jcp.29353
|View full text |Cite
|
Sign up to set email alerts
|

CXCL3 overexpression promotes the tumorigenic potential of uterine cervical cancer cells via the MAPK/ERK pathway

Abstract: CXCL3 belongs to the CXC-type chemokine family and is known to play a multifaceted role in various human malignancies. While its clinical significance and mechanisms of action in uterine cervical cancer (UCC) remain unclear. This investigation demonstrated that the UCC cell line HeLa expressed CXCL3, and strong expression of CXCL3 was detected in UCC tissues relative to nontumor tissues. In addition, CXCL3 expression was strongly correlated with CXCL5 expression in UCC tissues. In vitro, HeLa cells overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 36 publications
(47 reference statements)
0
39
0
Order By: Relevance
“…CXCL3 is one of the five up-regulated genes shared between G12D and G12V mice. Recent study has shown that CXCL3 overexpression can promotes the tumorigenic potential of uterine cervical cancer cells via the MAPK/ERK pathway 40 , and can be a potential therapeutic target for breast cancer 41 . Thus, CXCL3 could be a downstream target of mutant Kras.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL3 is one of the five up-regulated genes shared between G12D and G12V mice. Recent study has shown that CXCL3 overexpression can promotes the tumorigenic potential of uterine cervical cancer cells via the MAPK/ERK pathway 40 , and can be a potential therapeutic target for breast cancer 41 . Thus, CXCL3 could be a downstream target of mutant Kras.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, chemotherapy agents, including cisplatin, selectively inhibited regulatory and suppressor cells at low doses based on the previous study. 27 The results of our bioinformatics analysis showed that several anti-tumor chemokines [28][29] were identi ed to be enriched in the immunotype A group by bioinformatics analysis, while their role might be veiled by the coexistence of some pro-tumor molecules [30][31] . With the performance of ACT, the possibly diminished protumor feature might magnify the anti-tumor function in the microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…In study demonstrated here, we employed gene transfection to establish PHM1-41 cervical stromal cells overexpressing CXCL1, which can secrete a respectably high level of CXCL1 into medium, and the supernatants derived from medium of CXCL1 overexpressing PHM1-41cell can behave as a promoting mediator for the growth and migration of HeLa cells, indicating that a CXCL1 paracrine manner plays a crucial role in tumor-associated malignant behaviors. Coupled with this, our laboratory also previously revealed the critical CXCL3-paracrine mechanism, by which supernatants derived from stromal cells overexpressing CXCL3 raised the abilities of HeLa cell growth and migration [33].…”
Section: Discussionmentioning
confidence: 72%